An investigation of platelet parameters in smoking patients with coronary slow flow detected during coronary angiography - İnanır, Mehmet (Journal of Surgery and Medicine, 2020)
Aim: Coronary slow flow (CSF), which is linked to increased morbidity and mortality, is associated with atherosclerosis, and considered a variant of coronary artery disease (CAD). CSF is more common in smoking patients. We aimed to evaluate laboratory parameters, especially platelet indices, in smoking patients with CSF. Methods: Patients were selected from those who underwent coronary angiography (CAG) between January 2017 and October 2019. CAG records of 7287 patients were screened retrospectively for our case-control study. Procedures were carried out to identify ischemic heart disease based on clinical indications. CAG was performed in patients with positive non-invasive stress tests and/or high clinical suspicion for atherosclerotic CAD. Smoking patients with CSF (n=226) constituted the study group and matched number (n=226) of smoking patients with NCA were included in the control group. The demographic characteristics of all patients were recorded. Hematologic and biochemical parameters of all subjects were recorded and evaluated. Results: LDL cholesterol, triglyceride, total cholesterol, ALT, CRP, MCV, RDW, platelet count, PDW, MPV, PCT, and PLR levels were higher in smoking patients with CSF (study group) than normal coronary artery patients (control group) (P=0.034, P=0.015, P=0.033, P=0.006, P<0.001, P=0.033, P=0.021, P=0.039, P=0.006, P=0.010, P=0.021 and P=0.008, respectively). HDL cholesterol was found lower in smoking patients with CSF compared to controls (P=0.007). Conclusion: According to our results, high platelet parameters may play a role in coronary flow pathogenesis. The height of platelet parameters may indicate the presence of CSF. Our findings support the evidence for inflammation and platelet dysfunction in smoking patients with CSF. Extensive studies at a randomized molecular level are needed to demonstrate this relationship.